THE ROLE OF THE STATE IN ISLAMIC ECONOMICS LAW IN THE LIGHT OF ABBAS MIRAKHOR'S THOUGHTS - Hadi, Mohammad (International Significance of Notary, 2022)
Islamic economics is a progressive and dynamic economy. Various new theories have been raised as an offer for the development of Islamic economics law, one of which is done by Abbas Mirakhor. This article discusses role of the state to the main principles of the Islamic economics system. To find out more about the Islamic economic thought offered by Abbas Mirakhor, from the main principles of the economic system to the role of the state in the economy. This article uses a qualitative type of research using literature research. The results of this study show that Abbas is a reputable practitioner of Islamic economics and finance in the world, both Islamic and Western, and is highly respected in the Islamic world. Mirakhor is considered a reformer in Islamic economics law, and is part of the Iqtishad school. In the field of Islamic economic system, Mirakhor argues that the main principle of Islamic economic system requires distribution in two mechanisms, namely freedom, and justice, without which prosperity will not be achieved. Therefore, there is a need for a hermeneutical approach to answer various problems that occur in the Islamic economic system. In the context of the state, according to Mirakhor, the state has a very significant role in the welfare of society, especially through productive policies. The state must also be present in realising justice in society. There is a need for a hermeneutical approach to answer various problems that occur in the Islamic economic system. In the context of the state, according to Mirakhor, the state has a significant role in the welfare of society, especially in productive policies. The state plays a very significant role in the welfare of society, especially through its productive policies. The state must also be present in realising justice in society. There is a need for A hermeneutical approach to answer various problems that occur in the Islamic economic law. In the context of the state, according to Mirakhor, the state has a very significant role in the welfare of society, especially through productive policies. The state must also be present in realising justice in society.Keywords: Abbas Mirakhor, Islamic Economics Law, Role of the State